Rural Transformation in India: Deagrarianization and the Transition from a Farming to Non-farming Economy. Issue 2 (June 2020) - Majumdar, Koustab
Rural transformation in general has been conceptualized as modernization, rural development, changes in economic structure, and the migration of the population from the farming sector to the non-farming sectors of the economy. Different theoretical approaches (unidimensional and multidimensional) have been applied to the study of rural transformation, and these approaches have involved different indicators to examine the nature and magnitude of rural change/transformation. The rural development approach to the study of rural transformation has been criticized on the grounds that rural transformation does not always involve development. This article examines the Indian experience and contends that India's rural transformation has involved migration from the farming sector into the non-farming sectors and the de-agrarianization of the Indian economy.